Reconsidering End-User Experience of Circular Product Design - Warell, Anders V. (International Conference NordDesign 2024, Reykjavik, Iceland, 2024-08-12 - 2024-08-14, 2024)
Considering end-users is key in the transition towards the circular economy. Without the participation of the user, the circular economy will not be realized. However, in order to engage, users need to perceive the opportunity of contributing to the circular economy, and the product must include the user through activities that support circular goals. In this paper, the perceptual product experience of circular product design is explored and opportunities for circular user experience are identified.
Keywords: Circular Design Strategies; Circular Economy; Inclusion; Perception; User Experience